Triboelectric nanogenerator for a repairable transistor with self-powered electro-thermal annealing. (October 2020) - Kim, Weon-Guk; Han, Joon-Kyu; Tcho, Il-Woong; Park, Jun-Young; Yu, Ji-Man; Choi, Yang-Kyu
Abstract: A metal-oxide-semiconductor field-effect transistor (MOSFET), which is an elementary unit of microelectronics, was repaired by self-powered electro-thermal annealing with the aid of a wind-driven triboelectric nanogenerator (TENG). It was thermally cured by Joule heat that originated electrically from the MOSFET itself. The configuration of the self-curable system is composed of a MOSFET with an embedded built-in Joule heater and a wind-driven TENG. This self-curable feature is attractive for the construction of remote wireless sensor networks, is capable of sustainable operation for long-term use, has high immunity against external environmental stress as well as internal operation stress, and can reduce labor during the periodic replacement of power sources. Highlights: Self-powered electro-thermal annealing was performed to cure the damaged electronic devices. Electrical output of triboelectric nanogenerator was firstly used as Joule heat generation. The electronic device was successfully cured by the SP-ETA from plural damage factors: γ-ray and hot carrier injection. The Self-powered electro-thermal annealing was also verified at charge-trap based flash memory devices.